2018
DOI: 10.1038/bjc.2018.11
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Prostate-specific antigen velocity in a prospective prostate cancer screening study of men with genetic predisposition

Abstract: Background: Prostate-specific antigen (PSA) and PSA-velocity (PSAV) have been used to identify men at risk of prostate cancer (PrCa). The IMPACT study is evaluating PSA screening in men with a known genetic predisposition to PrCa due to BRCA1/2 mutations. This analysis evaluates the utility of PSA and PSAV for identifying PrCa and high-grade disease in this cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
1
0
0
Order By: Relevance
“…An analysis of the baseline screen for nearly 2500 men enrolled in IMPACT supported the use of targeted PSA screening in BRCA1/2 mutation carriers, suggesting that screening detects a high proportion of clinically significant tumours [22]. Moreover, we have also demonstrated that PSA is more predictive of PrCa in BRCA1/2 carriers than in noncarriers [23]. It has been reported that men with germline BRCA1/ BRCA2 mutations, on active surveillance for low-risk PrCa, are at a higher risk of reclassification to higher-grade PrCa than noncarriers [24].…”
Section: Introductionsupporting
confidence: 54%
“…An analysis of the baseline screen for nearly 2500 men enrolled in IMPACT supported the use of targeted PSA screening in BRCA1/2 mutation carriers, suggesting that screening detects a high proportion of clinically significant tumours [22]. Moreover, we have also demonstrated that PSA is more predictive of PrCa in BRCA1/2 carriers than in noncarriers [23]. It has been reported that men with germline BRCA1/ BRCA2 mutations, on active surveillance for low-risk PrCa, are at a higher risk of reclassification to higher-grade PrCa than noncarriers [24].…”
Section: Introductionsupporting
confidence: 54%